Reversible Confluent Deep White Matter Abnormalities: A New Variant of Posterior Reversible Encephalopathy Syndrome. (3rd December 2013) - Li, Yuebing; Castaldo, John; Bemporad, Joshua; Yacoub, Hussam A.
Abstract : We describe a confluent deep white matter abnormalities variant of PRES, further strengthening the notion that PRES is a disorder of radiological heterogeneity. We present 2 cases of PRES with findings of diffuse but reversible vasogenic edema located in the deep periventricular white matter regions of bilateral hemispheres without a clearly posterior distribution. We feel that this represents a rare variant of PRES on imaging, thus adding to the existing radiological spectrum for this entity. Both of our patients presented with malignant hypertension (mean arterial blood pressure of 200 mmHg) and developed neurological symptoms that included encephalopathy, seizure, headache, and vision changes. Additionally, both patients presented with significant subcortical white matter edema that improved dramatically on follow-up imaging. The clinical and radiological improvement in both patients occurred following successful blood pressure management. It is possible that the deep white matter changes of PRES are seen exclusively in the setting of severe accelerated hypertension. Our case reports reveal that, in patients with hypertensive encephalopathy, a deep white matter pattern of diffuse signal changes may not necessarily indicate chronic ischemic changes and follow-up imaging studies are essential to rule out a diagnosis of PRES.